Integration of international stock markets in light of the financial crisis : an analytical study of a sample of international stock markets - ميثم ربيع هادي; هبة الله مصطفى السيد (Iraqi Journal for Administrative Sciences, 2024)
The growth and overlap of global economies has increased the speed of capital movement, due to the legislative and legal liberalization of the international financial markets, which facilitated investment in foreign markets. economic globalization has pushed markets to integrate with one another. International diversification under the fragmentation of financial markets will reduce exposure to private and limited risks to a particular economy. It protects investors from major losses when certain financial markets face a sudden crisis as markets disintegrate. The aim of this study is to indicate whether the international stock markets are integrated and whether their integration is affected by the financial crisis compared to what before and after. This study also aims to try to resolve the controversial knowledge about the integration of markets during the financial crisis in light of the work environment in disparate economies in terms of the degree of economic development (Developed, Advanced Emerging, Secondary Emerging, Frontier) , And the diagnosis of the places that had the impact of the crisis stronger through examining the structure of linkages between international markets and the statement of time, place, size and direction of the impact of the crisis and the correlation of all of the degree of integration of markets or not. The study conducted a detailed analysis of the integration of financial markets during the financial crisis in the light of the data obtained for the study sample of indicators of the Iraqi and international stock markets , The latter was selected according to the classification of the Foundation (FTSE) For a sample of (53) international stock market, was the introduction of the Iraqi market for securities in the sample the fact that the study is interested in the study and knowledge of the extent of integration or fragmentation of the Iraqi market for international markets under shadow of the financial crisis for the perspective of the local Iraqi investor. The study period included (771) trading days for the sample studied as a whole, and started on (13/9/2006) until (26/05/2011). For the purpose of knowing the extent of integration of financial markets during the crisis compared to what preceded it, the sampling period was divided into three periods and equally for each period (257) days. using many financial and statistical methods, the study reached a number of conclusions, the most important of which are: The markets are not integrated under shadow of the financial crisis. and that the integration of markets affected by the financial crisis, however, the Iraqi investor can achieve returns from international investment compared to domestic investment, because of the Iraqi market and its connection to the opposite of international markets. The study went out with a number of recommendations, perhaps the most important of which is: The Iraqi investor should move from the local environment to the international environment for financial investment because there are sufficient benefits from international investment in those markets. As the correlation coefficients vary, the Iraqi investor will be able to reap the benefits of international investment. Moreover, investors should be patience and invest in the long term so as to remedy the effects of fluctuations that could occur in the financial markets; It has been proven experimentally that these fluctuations could fade and disappear over time and in the long term.